The effect of nanoclay on the tensile properties of PLA-kenaf fibre hybrid bionanocomposite - Anuar, Hazleen; Fuad, Faizah; Kaiser, Mohammad Rejaul; Ahmad, Zuraida; Abdul Razak, Shamsul Bahri (2011)
Hybrid bionanocomposite based on polylactic acid (PLA), kenaf fibre (KF) and organo montmorillonite (OMMT) was developed for food packaging application. Kenaf a tropical crop of Malaysia offered low cost and density, renewable and less abrasion to the processing equipment. In this project, PLA-KF-OMMT was extruded using twin screw extruder and then injection moulded for tensile properties measurement. Tensile strength and modulus of PLA-KF biocomposite significantly improved with 20 wt% kenaf fibre. Brittleness of PLA biocomposite however increased with kenaf fibre by reduction in elongation. As for PLA nanocomposite, the presence of 5 wt% OMMT showed remarkable improvement in tensile strength. Hybridization of PLA-KF-OMMT bionanocomposite on the other hand decreased both the tensile strength as well as tensile modulus. It is therefore hypothesized that effectiveness of load transfer at the interface was affected by the difference in shapes and aspect ratios of both types of reinforcement.